Cementless femoral components in bicondylar hybrid knee arthroplasty in patients with rheumatoid arthritis: A 10-year survivorship analysis. (23rd June 2017) - Hotfiel, Thilo; Carl, Hans-Dieter; Eibenberger, Teresa; Gelse, Kolja; Weiß, Julian; Jendrissek, Andreas; Swoboda, Bernd
Background: Total knee arthroplasty (TKA) has been established as a successful surgical treatment in the late stages of rheumatoid joint destruction. The purpose of this study was to review the clinical outcome and survivorship in rheumatoid arthritis (RA) patients undergoing TKA in hybrid technique with a cementless fixation of the femoral component. Methods: We analysed retrospectively 66 RA patients who underwent 72 TKAs (P.F.C. Sigma®). Mean follow-up time was 124 ± 41 months. To evaluate postoperative clinical outcome, knee injury and osteoarthritis outcome score (KOOS) and Oxford knee score (OKS) were assessed. Kaplan–Meier analysis was used to calculate survivorship. The primary outcome was revision for any reason. Results: Thirty-four patients (36 knees) died and two patients (2 knees) were lost to follow-up. Three patients (four knees) did not agree to participate. Twenty-seven patients (30 knees) were available for assessing clinical scores. The average scores were 85 ± 14 for KOOS and 34 ± 10 for OKS. In three patients (three knees), revision was necessary, including restricted range of motion ( n = 1), instability ( n = 1), and infection ( n = 1). There were no cases of loosening in this cohort study. The survival rates were 100% at 5 years, 97.1% at 10 years (95% CI 89.0–99.2%) and 95.6% at 15 years (95% CI 86.9–98.5%). Conclusions: This study confirms that excellent clinical results and a good 10-year survivorship can be obtained with hybrid fixation technique in TKA in the unique population of RA patients.